DEVELOPMENT AND CONTRADICTIONS IN THE LEGISLATION ON PEASANTS IN THE RUSSIAN EMPIRE TO THE END OF XIX - BEGINNING OF XX CENTURIES - Natalia Y. Belokopytova (Современная наука и инновации, 2022)
In the article the analysis of the content and contradictions of the main normative le-gal acts of the reform of 1861, the policy of counter reforms and its normative incarnation, defined the role of the reform of 1861 in development of agrarian reform P. A. Stolypin.